Analisis Pengaruh Faktor Organisasional, Individual, Situasional, dan Demografi Terhadap Niat Melakukan Whistleblowing Internal - Amelia Sinaga; Christina Dwi Astuti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
The purpose of this research is to analyze the influence of organizational, individual, situasional, and demographic factors on internal whistleblowing intentions. The sample of this empirical study is employees of Indonesian Power in Jakarta with a total of 150 questionnaires were distributed. Intake of total sample using purposive sampling method and the method of analysis used is the method of Multiple Regressions Analysis. The results of this empirical study are the locus of control, seriousness of wrongdoingand status of wrongdoerhave significant effect on internal whistleblowing intentions, whereas managerial status, organizational commitment and ethnic group do not have significant effect on internal whistleblowing intentions. Managerial status, locus of control, organizational commitment, seriousness of wrongdoing, status of wrongdoer and ethnic groupsimultaneously effect on internal whistleblowing intentions.